The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1124/jpet.113.204743
|View full text |Cite
|
Sign up to set email alerts
|

Survivin Inhibitor YM-155 Sensitizes Tumor Necrosis Factor– Related Apoptosis-Inducing Ligand-Resistant Glioma Cells to Apoptosis through Mcl-1 Downregulation and by Engaging the Mitochondrial Death Pathway

Abstract: Induction of apoptosis by the death ligand tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promising antitumor therapy. However, not all tumor cells are sensitive to TRAIL, highlighting the need for strategies to overcome TRAIL resistance. Inhibitor of apoptosis family member survivin is constitutively activated in various cancers and blocks apoptotic signaling. Recently, we demonstrated that YM-155, a small molecule inhibitor, downregulates not only survivin in gliomas but also myeloid ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…Single agent studies. We next determined the sensitivity of the cell lines to chemotherapy drugs used to treat DHL, as well as bortezomib, currently used for the treatment of myeloma and mantle cell lymphoma, and YM-155, an inhibitor of expression of Mcl-1 and survivin [16][17][18] . The DHL cell lines were sensitive to nM concentrations of MTX, cytarabine, doxorubicin, and, bortezomib, a proteasome inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Single agent studies. We next determined the sensitivity of the cell lines to chemotherapy drugs used to treat DHL, as well as bortezomib, currently used for the treatment of myeloma and mantle cell lymphoma, and YM-155, an inhibitor of expression of Mcl-1 and survivin [16][17][18] . The DHL cell lines were sensitive to nM concentrations of MTX, cytarabine, doxorubicin, and, bortezomib, a proteasome inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were seeded in 96-well plates (5000 cells/ well) in 100 ml of growth medium and incubated at 37°C for 24 hours before the addition of inhibitors or vehicle for 3 days. Cell growth assays were done using the CellTiter96 Aqueous Non-Radioactive Cell Proliferation Assay kit (Promega, Madison, WI), per manufacturer's instructions, to evaluate the effect the inhibitors and doses as described previously (Premkumar et al, 2013b). Absorbance was measured at a wavelength of 490 nm, and the absorbance values of treated cells are presented as a percentage of the absorbance of untreated cells.…”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis induction in vehicle-or inhibitor-treated cells was assayed by the detection of membrane externalization of phosphatidylserine using an annexin V assay kit (Molecular Probes, Invitrogen) as described previously (Premkumar et al, 2013b). Cells (2 Â 10 5 ) were harvested at various intervals after treatment, washed with ice-cold phosphate-buffered saline (PBS), and resuspended in 200 ml of binding buffer.…”
Section: Methodsmentioning
confidence: 99%
“…5C). As YM-155 has been proved to be a inhibitor of survivin [27], we co-treated the gastric cancer cells with YM-155 and TRAIL to evaluate the role of survivin in TRAIL-induced cytotoxicity. Our results showed that YM-155 significantly enhanced the TRAIL-induced cell death in BGC-823 and MGC-803 cells, similarly with miR-494 (Fig.…”
Section: Mir-494 Sensitizes Gastric Cancer To Trail Through Inhibitiomentioning
confidence: 99%
“…As overexpression of survivin has been reported to be responsible for inhibition of mitochondrial apoptosis [27], we next investigated the effect of miR-494 on regulating the TRAIL-induced mitochondrial apoptosis pathway. Results of flow cytometry showed that the TRAIL-induced decrease of mitochondrial membrane potential can be expanded by miR-494.…”
Section: Mir-494/survivin Axis Regulates Trail-induced Mitochondrial mentioning
confidence: 99%